Application of simple fed-batch technique to high-level secretory production of insulin precursor using Pichia pastoris with subsequent purification and conversion to human insulin - Chugh Dipti; Gäbel Thomas; Adnan Ahmad; Skoko Natasa; Polez Sulena; Gurramkonda Chandrasekhar; Swaminathan Sathyamangalam; Khanna Navin; Tisminetzky Sergio; Rinas Ursula (Microbial Cell Factories, 2010)
Abstract Background The prevalence of diabetes is predicted to rise significantly in the coming decades. A recent analysis projects that by the year 2030 there will be ~366 million diabetics around the world, leading to an increased demand for inexpensive insulin to make this life-saving drug also affordable for resource poor countries. Results A synthetic insulin precursor (IP)-encoding gene, codon-optimized for expression in P. pastoris, was cloned in frame with the Saccharomyces cerevisiae α-factor secretory signal and integrated into the genome of P. pastoris strain X-33. The strain was grown to high-cell density in a batch procedure using a defined medium with low salt and high glycerol concentrations. Following batch growth, production of IP was carried out at methanol concentrations of 2 g L-1, which were kept constant throughout the remaining production phase. This robust feeding strategy led to the secretion of ~3 gram IP per liter of culture broth (corresponding to almost 4 gram IP per liter of cell-free culture supernatant). Using immobilized metal ion affinity chromatography (IMAC) as a novel approach for IP purification, 95% of the secreted product was recovered with a purity of 96% from the clarified culture supernatant. Finally, the purified IP was trypsin digested, transpeptidated, deprotected and further purified leading to ~1.5 g of 99% pure recombinant human insulin per liter of culture broth. Conclusions A simple two-phase cultivation process composed of a glycerol batch and a constant methanol fed-batch phase recently developed for the intracellular production of the Hepatitis B surface antigen was adapted to secretory IP production. Compared to the highest previously reported value, this approach resulted in an ~2 fold enhancement of IP production using Pichia based expression systems, thus significantly increasing the efficiency of insulin manufacture.